With Similar Visual Angles, Larger Displays Improve Performance on Spatial Tasks - Tan, Desney; Gergle, Darren; Scupelli, Peter G.; Pausch, Randy ((2003) CHI 2003 Conference on Human Factors in Computing Systems, 2003)
Large wall-sized displays are becoming prevalent. Although researchers have articulated qualitative benefits of group work on large displays, little work has been done to quantify the benefits for individual users. We ran two studies comparing the performance of users working on a large projected wall display to that of users working on a standard desktop monitor. In these studies, we held the visual angle constant by adjusting the viewing distance to each of the displays. Results from the first study indicate that although there was no significant difference in performance on a reading comprehension task, users performed about 26% better on a spatial orientation task done on the large display. Results from the second study suggest that the large display affords a greater sense of presence, allowing users to treat the spatial task as an egocentric rather than an exocentric rotation. We discuss future work to extend our findings and formulate design principles for computer interfaces and physical workspaces.